The virome investigation of the globally endangered Eld’s deer (Rucervus eldii) on Hainan Island, China - Haoxiang Su; Dandan Zheng; Zihan Li; Xuming Qi; Yunxing Chang; Guangxu Ren; Qingqing Lu; Jiaqi Li; Yu Li; Chuan Tian; Ruoyan Peng; Gaoyu Wang; et al. (Scientific Reports)
Abstract Eld’s deer (Rucervus eldii) is a rare and globally endangered tropical Southeast Asian deer species. There is no research on pathogens in Eld’s deer in Hainan, China. This study aimed to understand the virus diversity and novel viruses in Eld’s deer, and provided important epidemiological baseline information for conservation of this endangered species. 33 nasal swabs, 33 anal swabs, and 9 wound (bitten by ticks) swabs were collected from 33 wild Eld’s deer in a nature reserve in Hainan, which constituted into 5 pools. Based on next-generation sequencing (NGS) and macrogenomic analysis, there were differences in the 5 pools of viral reads, while the overall viral reads were closely related to mammals. The novel papillomavirus (PsPV-HMU-1) and Circular Rep-encoding (replication-associated protein encoding) single-stranded DNA (CRESS DNA) virus (PsaCV-HMU-1) were identified in Eld’s deer, with amino acid homology of the less than 77.20% of the L1 and less than 45.43% of the rep, respectively. PsPV-HMU-1 and PsaCV-HMU-1 are relatively independent on their phylogenetic trees, and with the overall prevalence of 24.24% (8/33) and 3.03% (1/33) in Eld’s deer, respectively. Our results expanded the viral genomic information and host range, and implied that it is necessary for continued epidemiological surveillance in order to understand pathogenicity and the potential for cross-species transmission of viruses in wild Eld’s deer.